Buffalo cheese whey proteins, identification of a 24 kda protein and characterization of their hydrolysates: in vitro gastrointestinal digestion - Bassan, Juliana C. [UNESP]; Goulart, Antonio J. [UNESP]; Nasser, Ana L. M. [UNESP]; Bezerra, Thaís M. S. [UNESP]; Garrido, Saulo S. [UNESP]; Rustiguel, Cynthia B.; Guimarães, Luis H. S.; Monti, Rubens [UNESP] (Public Library Science, 2015)
Milk whey proteins are well known for their high biological value and versatile functional properties, characteristics that allow its wide use in the food and pharmaceutical industries. In this work, a 24 kDa protein from buffalo cheese whey was analyzed by mass spectrometry and presented homology with Bos taurus beta-lactoglobulin. In addition, the proteins present in buffalo cheese whey were hydrolyzed with pepsin and with different combinations of trypsin, chymotrypsin and carboxypeptidase-A. When the TNBS method was used the obtained hydrolysates presented DH of 55 and 62% for H1 and H2, respectively. Otherwise for the OPA method the DH was 27 and 43% for H1 and H2, respectively. The total antioxidant activities of the H1 and H2 samples with and without previous enzymatic hydrolysis, determined by DPPH using diphenyl-p-picrylhydrazyl radical, was 4.9 and 12 mM of Trolox equivalents (TE) for H2 and H2Dint, respectively. The increased concentrations for H1 and H2 samples were approximately 99% and 75%, respectively. The in vitro gastrointestinal digestion efficiency for the samples that were first hydrolyzed was higher compared with samples not submitted to previous hydrolysis. After in vitro gastrointestinal digestion, several amino acids were released in higher concentrations, and most of which were essential amino acids. These results suggest that buffalo cheese whey is a better source of bioavailable amino acids than bovine cheese whey.